Between Dreams and Realities : Some Milestones in Pakistan's History - Sartaj Aziz; Foreword by Babar Ali, Syed (Karachi Oxford University Press, 2020)
This book attempts to demonstrate that only a genuine democratic dispensation can ensure its survival as a viable federation. Sartaj Aziz argues that the vitality of a nation comes primarily from the value system, cultural heritage, and social energy of its people.
Include Illustrations and Index
Keywords: Pakistan -- Politics and government -- Politicians